Bel canto a novel - Patchett, Ann (London HarperCollins, 2002)
Somewhere in South America, at the home of the country's vice president, a lavish birthday party is being held in honor of Mr. Hosokawa, a powerful Japanese businessman. Roxanne Coss, opera's most revered soprano, has mesmerized the international guests with her singing. It is a perfect evening -- until a band of gun-wielding terrorists breaks in through the air-conditioning vents and takes the entire party hostage. But what begins as a panicked, life-threatening scenario slowly evolves into something quite different, as terrorists and hostages forge unexpected bonds and people from different countries and continents become compatriots. Friendship, compassion, and the chance for great love lead the characters to forget the real danger that has been set in motion and cannot be stopped
1
Keywords: Victims of terrorism -- Fiction; Women singers -- Fiction